The Influence of Tourism Experience on the Image of Fishing Village: Taking Xunpu Village, Quanzhou City as an example - Ting LI; Ying XIONG; Yaqing LI; Aolun ZHAI; Jinhua CHEN (Haiyang Kaifa yu guanli, 2022)
In order to promote the development of China′s fishing village tourism and the implementation of the "Rural Revitalization" strategy, the paper studied the impact mechanism of tourism experience on the image of fishing village, the role of tourists′ perceived value and tourists′ risk perception, based on the field survey data of Xunpu village in Quanzhou City, then put forward development suggestions. The results showed that tourism experience had a significant positive impact on the image of fishing village. Tourists′ perceived value played an intermediary role in the impact mechanism of tourism experience on the image of fishing village. Tourists′ risk perception played a regulatory role between tourism experience and tourists′ perceived value, as well as between tourism experience and fishing village image. When tourists′ risk perception was low, tourism experience was easier to improve the fishing village image by improving tourists′ perceived value. The development of fishing village tourism in Xunpu village should focus on improving tourism experience and tourists′ perceived value, reducing tourists′ risk perception, and building a fishing village tourism brand.